The Role of Occupational Stress in the Association between Emotional Labor and Mental Health: A Moderated Mediation Model - Heyeon Park (Sustainability, 2019)
This study investigated whether occupational stress factors moderate the effect of emotional labor on psychological distress in call center employees. A cross-sectional and descriptive study using anonymous paper-based survey methods was conducted in a sample of 283 call center employees in South Korea. Participants completed the Emotional Labor Scale, the Depression Anxiety Stress Scale, and the Korean Occupational Stress Scale. Moderated mediation analyses were conducted using the PROCESS macro in order to investigate the relationship among variables. The results showed that the association between surface acting while having emotional labor and psychological distress was mediated by emotional dissonance. The mediated effect of emotional dissonance was moderated by discomfort in occupational climate, suggesting that improving the occupational environment can lessen the level of psychological distress among emotional workers, and that more attention should be devoted to the development of an intervention at the organizational level in order to prevent mental health problems in this population.